ANALISA NILAI SAIDI SAIFI SEBAGAI INDEKS KEANDALAN PENYEDIAAN TENAGA LISTRIK PADA PENYULANG CAHAYA PT. PLN (PERSERO) AREA CIPUTAT - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
The demand for electricity will continues to increase each time, this is because of the number of PLN’s customers will continues too to grow each year. Therefore, this is directly proportional to growing the amount of electricity that have to be streamed. With the increasing of the number of PLN’s customers, the provider (PLN) have to increase the amount of electricity supply as well. In the era of globalization, the efficiency of electrical power has always been the main issued, both from the providers and the customers. Therefore, the realibility of distribution system of electrical power will been the main issued as well. The index that showing the reliability of the distribution system of electrical power is SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interuption Frequency Index). As small as the value of the indexes, both SAIDI and SAIFI is so the more reliable the system, which means the efficiency of the distribution system is good (high efficiency). In this research will be discussed about the analysis of SAIDI and SAIFI values of Cahaya feeder, as well as how to suppress the value of SAIDI and SAIFI. Realibilty index SAIDI and SAIFI on Cahaya Feeder in the year of 2017 is 2.277 hours/costumers/year dan 2.406 time/costumers/years. That is reliable based on SPLN 59:1985 standard. Cost loss in year of 2017 due to outage on the Cahaya Feeder is IDR 12,794,305,-